Hourly Firewood Consumption Patterns and CO2 Emission Patterns in Rural Households of Nepal - Pokharel Tika Ram; Rijal Hom Bahadur (Designs, 2020)
Nepal has low per-capita energy use and a majority of its rural residents use firewood as their primary energy source. Excessive use of firewood in improperly ventilated buildings degrades the indoor environment and health condition of the inhabitants. This study aims to assess the influence of hourly firewood consumption patterns on CO2 emissions and resulting concentrations in rural households in Nepal. A field survey was conducted for 24 h in 16 households during winter. The results suggest that most of the households tend to use more firewood during the morning and evening hours. Family size and number of animals reared by the households were positively correlated with firewood consumption, whereas family size was negatively correlated with per-capita firewood consumption. Per-capita firewood consumption was found to be 1.8 kg/(capita·day). Household firewood consumption and CO2 emissions were 12 kg/(family·day) and 14.26 kg CO2 e/(household·day), respectively. The larger households spent more time for cooking, while their consumption rate was similar (1.3 kg/h) to that of smaller households. High indoor CO2 emissions in the morning and evening hours due to high firewood consumption may pose severe health risks to the inhabitants. Therefore, intensive awareness programs and pollution control programs are suggested for improving indoor air quality and health condition of the rural population.